Adipose Tissue Immunomodulation and Treg/Th17 Imbalance in the Impaired Glucose Metabolism of Children with Obesity - Stefania Croce; Maria Antonietta Avanzini; Corrado Regalbuto; Erika Cordaro; Federica Vinci; Gianvincenzo Zuccotti; Valeria Calcaterra (MDPI AG, 2021)
In the last few decades, obesity has increased dramatically in pediatric patients. Obesity is a chronic disease correlated with systemic inflammation, characterized by the presence of CD4 and CD8 T cell infiltration and modified immune response, which contributes to the development of obesity related diseases and metabolic disorders, including impaired glucose metabolism. In particular, Treg and Th17 cells are dynamically balanced under healthy conditions, but imbalance occurs in inflammatory and pathological states, such as obesity. Some studies demonstrated that peripheral Treg and Th17 cells exhibit increased imbalance with worsening of glucose metabolic dysfunction, already in children with obesity. In this review, we considered the role of adipose tissue immunomodulation and the potential role played by Treg/T17 imbalance on the impaired glucose metabolism in pediatric obesity. In the patient care, immune monitoring could play an important role to define preventive strategies of pediatric metabolic disease treatments.